Vertical structure of Antarctic tropospheric ozone depletion events: characteristics and broader implications - A. E. Jones; P. S. Anderson; E. W. Wolff; H. K. Roscoe; G. J. Marshall; A. Richter; N. Brough; S. R. Colwell (Atmospheric Chemistry and Physics, 2010)
The majority of tropospheric ozone depletion event (ODE) studies have focussed on time-series measurements, with comparatively few studies of the vertical component. Those that exist have almost exclusively used free-flying balloon-borne ozonesondes and almost all have been conducted in the Arctic. Here we use measurements from two separate Antarctic field experiments to examine the vertical profile of ozone during Antarctic ODEs. We use tethersonde data to probe details in the lowest few hundred meters and find considerable structure in the profiles associated with complex atmospheric layering. The profiles were all measured at wind speeds less than 7 ms −1 , and on each occasion the lowest inversion height lay between 10 m and 40 m. We also use data from a free-flying ozonesonde study to select events where ozone depletion was recorded at altitudes >1 km above ground level. Using ERA-40 meteorological charts, we find that on every occasion the high altitude depletion was preceded by an atmospheric low pressure system. An examination of limited published ozonesonde data from other Antarctic stations shows this to be a consistent feature. Given the link between BrO and ODEs, we also examine ground-based and satellite BrO measurements and find a strong association between atmospheric low pressure systems and enhanced BrO that must arise in the troposphere. The results suggest that, in Antarctica, such depressions are responsible for driving high altitude ODEs and for generating the large-scale BrO clouds observed from satellites. In the Arctic, the prevailing meteorology differs from that in Antarctica, but, while a less common effect, major low pressure systems in the Arctic can also generate BrO clouds. Such depressions thus appear to be fundamental when considering the broader influence of ODEs, certainly in Antarctica, such as halogen export and the radiative influence of ozone-depleted air masses.